DEVELOPMENT OF THE SELF SPIRITUAL AKLIAH (SSA) MODEL FOR CHARACTER EDUCATION AT PONDOK PESANTREN AINUL YAKIN - Husna Nashihin; La Hadisi; Abdul Holik; Zulkifli Musthan; Qiyadah Robbaniyah; Adi Haironi (Institut Agama Islam Al Hidayah Bogor, 2026)
Character education has become a fundamental objective of Islamic education in fostering students' moral integrity, spiritual awareness, and social responsibility. However, character education in many Islamic boarding schools remains largely conventional and lacks a systematic educational model, particularly for students with psychosocial mental disabilities following rehabilitation. This study aimed to develop and evaluate the effectiveness of the Self Spiritual Akliah (SSA)-Based Character Education Model at Pondok Pesantren Ainul Yakin. The study employed a Research and Development (R&D) approach based on the Borg and Gall model, encompassing needs analysis, planning, preliminary product development, expert validation, product revision, Focus Group Discussion (FGD), operational field testing, final product revision, and dissemination. Data were collected through observations, interviews, documentation, expert validation questionnaires, FGDs, and pretest–posttest assessments. Quantitative data were analyzed using Pearson Product-Moment validity testing, Cronbach's Alpha reliability testing, and Normalized Gain (N-Gain) analysis. The findings indicate that the SSA model was successfully developed into a valid, practical, and effective character education model. The research instrument demonstrated excellent reliability (Cronbach's Alpha = 0.938). Following a three-month implementation period, the mean character development score increased from 58.43 to 83.10, with an average N-Gain score of 0.60 (60.45%), indicating moderate improvement. The SSA model integrates the dimensions of Self, Spiritual, and Akliah into a holistic character education framework through habituation, mentoring, instructional activities, and continuous evaluation. The model provides an evidence-based approach that may serve as an alternative framework for strengthening character education in Islamic boarding schools and other inclusive Islamic educational institutions.